Two-dimensional polymers with versatile functionalities via gemini monomers - Li, Yang (Sci Adv, 2019)
Two-dimensional synthetic polymers (2DSPs) are sheet-like macromolecules consisting of covalently linked repeat units in two directions. Access to 2DSPs with controlled size and shape and diverse functionality has been limited because of the need for monomers to retain their crystallinity throughout polymerization. Here, we describe a synthetic strategy for 2DSPs that obviates the need for crystallinity, via the free radical copolymerization of amphiphilic gemini monomers and their monomeric derivatives arranged in a bilayer at solid-liquid interfaces. The ease of this strategy allowed the preparation of 2DSPs with well-controlled size and shape and diverse functionality on solid templates composed of various materials with wide-ranging surface curvatures and dimensions. The resulting 2DSPs showed remarkable mechanical strength and have multiple applications, such as nanolithographic resist and antibacterial agent. The broad scope of this approach markedly expands the chemistry, morphology, and functionality of 2DSPs accessible for practical applications.